Fallaxosides B1 and D3, triterpene glycosides with novel skeleton types of aglycones from the sea cucumber Cucumaria fallax. Issue 17 (27th April 2017) - Silchenko, Alexandra S.; Kalinovsky, Anatoly I.; Avilov, Sergey A.; Dmitrenok, Pavel S.; Kalinin, Vladimir I.; Berdyshev, Dmitrii V.; Chingizova, Ekaterina A.; Andryjaschenko, Pelageya V.; Minin, Kirill V.; Stonik, Valentin A.
Abstract: Two unprecedented triterpene glycosides, fallaxosides B1 and D3 with aglycones of new skeletal types were isolated from the sea cucumber Cucumaria fallax (Cucumariidae, Dendrochirotida). The first of these aglycones is formed as result of intramolecular aldol condensation of a precursor having 1, 6-diketone functionality, while the second one by pinacol-pinacolone-like rearrangement of another precursor, probably containing 7, 8, 9-trihydroxy fragment (or its 8, 9-epoxy-7-hydroxy analog). The structures of these compounds were established by analysis of 1D, 2D NMR, ESI MS and CD data with using the quantum-chemical calculations. Graphical abstract: